(untitled) (Bangladesh Journal of Botany, 2021)
Effects of boron as an essential nutrient for sugar beet along with gamma irradiation was traced under field conditions. Data demonstrated that the fresh and dry root yields of sugar beet significantly increased with the increase either gamma dose or boron levels comparing to the non-irradiated and born-untreated plants. It seems that root dry weight tended to increase gradually with increasing gamma dose 0 to 100 Gy, then tended to decrease with 200 Gy dose but it still increased with gradual increases of boron levels. In this regard, the best value of root dry weight was achieved with 100 Gy dose interacted with 2.40 kg/ ha of boron addition. On the other hand, plants exposed to 50 Gy and treated with 2.40 kg/ ha reflected the highest shoot dry matter yield compared to other treatments. Relatively, this treatment increased shoot dry weight by about one fold, two folds and near to two folds for the same sequence. Behavior of NPK uptake by shoots has the same trend. Plants irradiated with 100 Gy together with 2.40 kg boric acid ha-1 yielded the highest total soluble solids (TSS%) and produced the best per cent of sucrose. Bangladesh J. Bot. 50(4): 1041-1049, 2021 (December)